3D geo-database implementation using Craniofacial Geometric Morphometrics Database System - Suwardhi, Deni; Setan, Halim; Chong, Albert; Majid, Zulkepli; Ahmad, Anuar (2006)
Craniofacial Database System has been developed for storing, manipulation and analysis with Geometric Morphometrics concept. The main objective of the system is to store the normal craniofacial (face and/or skull) of Malaysian people. The ‘normal’ is used for reference in many areas such as surgical planning, forensic, gear protective design, and anthropology researches. The data with which we are working are surface scans. Typically these are triangular meshes, and may or may not have a texture image associated with them. The data can be obtained from photogrammetry system, laser scanning system, or iso-surfaces from volume images (CT or MRI images). Our geometrical model is based on existing standards of the Open GIS Consortium. There are new data types have been added to OpenGIS SQL Specification. They are Solid, Voxel, Tetrahedron, Pixel, Triangle, 3DRaster, TetrahedronMesh, 2DRaster, TriangularMesh, Node and Vertices. Implementation in PostGIS, extension module for PostgreSQL ORDBMS, was done. PostGIS follows the OpenGIS "Simple Features Specification for SQL". Some functions to enable spatial queries were added by C language. The modification is called PostGISPlus (PostGIS+). Because of characteristic of the geometrical data model is similar with geospatial data then we try to implement 3D geo-database in our developed database system. This paper reports the problems and their solutions in the implementation